Purwoceng (Pimpinella pruatjan Molk.) nanosuspension repairs spatial white albino wistar strains’ spatial memory degeneration after sleep deprivation - Rangga Wisnu Wardana; Tuti Sri Suhesti; Fitranto Arjadi (Department of Biology, Faculty of Sci and Tech, Universitas Islam Negeri Alauddin Makassar, 2022)
.